PREVALENCE BY CRITERION BASIS FOR POLYCYSTIC OVARY SYNDROME AMONG WOMEN PRESENTING WITH AMENORRHEA AND OLIGOMENORRHEA AT THE KENYATTA NATIONAL HOSPITAL IN 2018 (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2020)
Background: Polycystic ovary syndrome (PCOS) is the commonest endocrinological condition associated  with anovulatory infertility in women. Worldwide, the prevalence is highly variable, ranging from 2.2% to  as high as 26%. Similarly, the prevalence of PCOS is variable in Africa, occurring in about 1 in 6 infertile  Nigerian women and 32% of infertile women in Tanzania. The variable prevalence could be attributable  to multiplicity of diagnostic criteria, and similarity in presentation with other syndromes that present with  amenorrhea and the population studied. Objectives: To determine the prevalence by criterion basis of PCOS among women with amenorrhea and  oligomenorrhea attending the Kenyatta National Hospital in 2018. Methodology: This was a descriptive cross sectional study. The study population comprised of 131 women  recruited at Kenyatta National Hospital gynecology department. Those enrolled, gave an informed consent,  filled a questionnaire, had their anthropometric measurements taken, then underwent a pelvic ultrasound scan  and a blood sample for serum free testosterone levels was taken. PCOS was determined using the Rotterdam  2003, the NIH 1990 and the AE-PCOS 2006 criteria. Results: PCOS was diagnosed in 49(37%) using the Rotterdam criteria, 26(20%) using the NIH 1990 criteria  and 15(12%) using the AE-PCOS 2006 criteria.  Conclusion: When the Rotterdam criteria is used, the prevalence is highest, followed by the NIH 1990 and  lastly the AE-PCOS 2006. Recommendation: The Rotterdam criteria for diagnosis of PCOS should be used as it more representative.